Padrões alimentares e sua associação com a pressão arterial em adolescentes - Neves, Morgana Egle Alves (2020)
The diet is a potential modifiable risk factor for chronic non-communicable diseases, such as obesity and high blood pressure, especially in adolescence, a phase marked by intense biological, physical and psychological changes that affect the formation of eating habits. In this context, the assessment of food consumption through the identification of dietary patterns has been an important tool, allowing to analyze the role of diet as an exposure variable for health outcomes. Thus, this work consists of two manuscripts. The first aimed to conduct a systematic review of observational studies that investigated the association between dietary patterns identified by multivariate methods and markers of body adiposity and blood pressure in adolescents, evaluating possible influences of the method used in the extraction of the patterns. In this manuscript, fourteen studies found a significant association between dietary patterns and markers of body adiposity and blood pressure. Observing that the use of the Reduced Rank Regression (RRR) method to extract dietary patterns provided a greater frequency of association between dietary patterns and outcomes. After conducting a systematic literature review, it was decided to identify dietary patterns, using RRR, and to analyze their association only with blood pressure in Brazilian adolescents. Thus, for the second manuscript, a probabilistic sample of 36,956 adolescents aged 12 to 17 years, participating in ERICA, was evaluated. ERICA is a multicenter, school-based, nationwide sectional study carried out in 2013-2014. The adolescents' systolic and diastolic blood pressure means were considered as a dependent variable. Food consumption was estimated from the 24-hour recall (REC24h). 1128 food items were reported, which were grouped into 28 groups, according to nutritional characteristics and usual frequency of consumption. The x scores produced by the RRR were considered as independent variables. Linear regression models were used to assess the association between dietary pattern scores and blood pressure. Three dietary patterns were identified, the “Diet” food pattern, characterized by the positive consumption of “diet / light” foods, chicken and preparations, vegetables, vegetables and spices, red meats and preparations, tubers and drinks with added sugar and negative of cookies, rice and preparations, beans and preparations, sweet breads, cakes and pies and sweetened milk drinks, was inversely associated with systolic and diastolic blood pressure in obese Brazilian adolescents.